SPORTIVE STRESS AND ITS IMPACT ON THE IMMUNE STATE OF ATHLETES DEALING WITH FREESTYLE WRESTLING (Experimental biology, 2023)
The article is dedicated to the study of the effect of physical loads on the maintenance and functional activity of lymphocytes in the peripheral blood system of freestyle wrestlers in the dynamics of the training macrocycle. Because of the impact from physical loads, a decrease occurs in the content of lymphocytes and their functional activity is reduced. Those changes depend on the intensity of physical loads; they become maximal at the end of the competition period and minimal in the transition period. It may be assumed that the immune system plays a significant role in the adaptation of the body to significant physical loads. The results of the conducted study show that the characteristics of cellular immunity are formed in wrestlers already at an early stage of sports training. It happens partly because of the presence of static pathology, associated with the reaction to physical loads within the framework of the training process. An enhanced immunological examination of wrestlers with an assessment of the mitochondrial activity of the lymphocyte population enables us to evaluate the individual threshold level of physical loads, the excess of which leads to a disturbance of the immune metabolism. Therefore, the inclusion of an additional transitional period in the training macrocycle helps to a more complete recovery of the studied indicators.